Analisis Diferensiasi Tingkat Konsumsi pada Generasi Y dan Generasi Z yang Dipengaruhi oleh Digitalisasi, Sosial, dan Demografi - Awaluddin Siahaan; Fitrawaty Fitrawaty; Indra Maipita (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze the influence of digitalization and social factors on the consumption levels of Generation Y and Generation Z by considering generation and demographic variables as moderating factors. The study employed a quantitative approach using primary data collected through questionnaires distributed to 200 respondents in Medan City. Likert-scale data were transformed from ordinal to interval scales using the Method of Successive Interval (MSI). Data analysis was conducted using the Moderated Multiple Regression (MMR) method to examine the direct effects of the independent variables and the moderating roles of generation and demographic variables. The results indicate that digitalization and social factors have a positive and significant effect on consumption levels. Generation and demographic variables also show a positive and significant influence on public consumption levels. However, the moderation test results reveal that neither generation nor demographics moderate the relationship between digitalization and social factors on consumption levels. These findings suggest that the influence of digitalization and social factors on consumption tends to be relatively consistent across different generational and demographic groups. This study confirms that digitalization is the dominant factor influencing consumer behavior in the digital economy era, supported by social environmental influences as well as generational and demographic characteristics.